Solid Dispersion System Candesartan-cilexetil Mannitol Co-Grinding Method - Rahayu, Feronika Evma; Silvyana, Annysa Ellycornia; Warti, Lia; Umar, Salman; Rosaini, Henni (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2023)
Research on solid dispersion systems had been done to improve physicochemical characteristics and the dissolution rate of candesartan-cilexetil a had been conducted. Candesartan cilexetil is included in BCS (Biopharmaceutical Classification System) class II, which has low solubility and high permeability which causes poor absorption of drugs in the digestive tract. Solid dispersions were prepared through the grinding method using mannitol. The formula with 3 comparisons between candesartan-cilexetil and mannitol 1:1, 1:3, and 1:5. A mixture of physics of candesartan cilexetil-mannitol was made without a solid dispersions system which was 1:1 as a comparison. Solid dispersion formed was characterized by particle size distribution analysis, Fourier transforms infrared (FT-IR), X-ray diffraction, scanning electron microscopy (SEM), differential scanning calorimetry (DSC), determination rate, and dissolution test. The result particle size distribution analysis showed grinding method there were solid dispersions mixed perfectly. The FT-IR of this analysis showed no interaction between candesartan-cilexetil mannitol in solid dispersion powder. The result of X-ray diffraction showed a decrease in crystallization degree. The DSC result showed a shift in endothermic peak candesartan-cilexetil. The manufacture of a solid dispersion system of candesartan-cilexetil mannitol can improve the physicochemical characteristics and the dissolution rate of candesartan-cilexetil compared with physical mixtures. The result in the dissolution was solid dispersion 1 = 53.1990 %, solid dispersion 2 = 54.3621 %, and solid dispersion 3 = 62.3621 %. The statistical result of dissolution efficiency using the Kruskal-Willis test with significant = 0.009(< 0.05) showed the difference among the dissolution efficiency of candesartan-cilexetil, physical mixture, and each solid dispersion.